1990
DOI: 10.1111/j.1475-682x.1990.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Leisure as a Primary Institution

Abstract: The authors argue that leisure should be considered a primary institution in advanced industrial societies. The increasingly organized nature of contemporary leisure and the prominence of leisure activities in the search for communal bonds are viewed as the primary factors contributing to the emergence of leisure as a major social institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
4
2
Order By: Relevance
“…While our data did not provide evidence in support of this proposition (i.e., identity affirmation's nonsignificant effect), other authors have argued that the symbolic value of leisure activities has a significant influence on the selection of activities (e.g., Bourdieu, 1977Bourdieu, , 1984Dimanche & Samdahl, 1994;Frey & Dickens, 1990;Rojek, 1990;Urry, 1990;Veblen, 1899). Veblen (1899) asserted that leisure consumption has symbolic meanings which people use to reflect their association with a certain social class.…”
Section: Discussioncontrasting
confidence: 93%
“…While our data did not provide evidence in support of this proposition (i.e., identity affirmation's nonsignificant effect), other authors have argued that the symbolic value of leisure activities has a significant influence on the selection of activities (e.g., Bourdieu, 1977Bourdieu, , 1984Dimanche & Samdahl, 1994;Frey & Dickens, 1990;Rojek, 1990;Urry, 1990;Veblen, 1899). Veblen (1899) asserted that leisure consumption has symbolic meanings which people use to reflect their association with a certain social class.…”
Section: Discussioncontrasting
confidence: 93%
“…Specifically, riders should blindly adhere to the values and commodities marketed to them, and they should derive a sense of pseudo-individualism from participating in the culture and should be alienated. Other research has found the theory to be overly deterministic and suggests that recreational pursuits can be an important source of community and personal fulfillment, and our results were no different (e.g., Frey and Dickens 1990; Rosenbaum 2013; Comer 2011).…”
Section: Species-being and Serious Ridingcontrasting
confidence: 49%
“…Based on this conceptual perspective of symbolic meaning, people who are conscious of self-reflection in consuming products tend to affiliate more closely with groups that they perceive share similar values or belong to their social class (Hirschman, 1981). This is true within a leisure context (Dimanche & Samdahl, 1994;Frey & Dickens, 1990;Rojek, 1990). For example, there are individuals who would never stay overnight at an economy class hotel because it is "beneath them."…”
Section: Sign Valuementioning
confidence: 94%